Iodine induced 1-D lamellar self assembly in organic ionic crystals for solid state dye sensitized solar cells. Issue 41 (11th October 2017) - Vaghasiya, Jayraj V.; Sonigara, Keval K.; Beuvier, Thomas; Gibaud, Alain; Soni, Saurabh S.
Abstract : A novel saturated heterocyclic organic ionic crystal, piperidinium iodide (PiHI), is synthesized by a facile route and applied as a solid electrolyte in Dye Sensitized Solar Cells (ss-DSSCs). Abstract : A novel saturated heterocyclic organic ionic crystal, piperidinium iodide (PiHI), is synthesized by a facile route and applied as a solid electrolyte in Dye Sensitized Solar Cells (ss-DSSCs). Upon addition of a small quantity of iodine, PiHI self-assembles into a 1D lamellar micro crystalline structure that shows anisotropic conductivity. The two-component PiHI was characterized by using electrochemical impedance spectroscopy, cyclic voltammetry, steady state voltammetry, FT-IR, and Raman spectroscopy. Wide angle X-ray diffraction (XRD) measurement confirms the presence of long range 1D lamellar channels that pave the way for the diffusion of the redox couple I − /I3 − and exhibit high anisotropic conductivity. The ionic conductivity of 1D PiHI (with I2 ) aligned perpendicular to the electrode, σ ⊥ (15.46 mS cm −1 ), is 1.5 times higher than that aligned parallel to the electrode σ ∥ = 10.32 mS cm −1 . The ss-DSSC devices with these self-assembled ordered ionic crystals with a carbazole based sensitizer (SK1) achieved a power conversion efficiency (PCE) of 4.2% and 5.2% for ∥ al and ⊥ ar arrangement, respectively. The reported PCEs are better than that obtained from a classical liquid electrolyte with SK1 sensitizers. The electron kinetics at various interfaces of ss-DSSC devices was evaluated using Electrochemical Impedance Spectroscopy (EIS) measurements. The presence of a saturated cyclic structure promotes close packing through H-bonding and electrostatic interactions, which make ss-DSSC devices more stable up to 600 h under illumination of 1 sun.